2021
DOI: 10.1021/jacs.1c01863
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Dephasing along the Reaction Coordinate of an Electron Transfer Reaction

Abstract: The role of molecular vibration in photoinduced electron transfer (ET) reactions has been extensively debated in recent years. In this study, we investigated vibrational wavepacket dynamics in a model ET system consisting of an organic dye molecule as an electron acceptor dissolved in various electron donating solvents. By using broad band pump−probe (BBPP) spectroscopy with visible laser pulses of sub-10 fs duration, coherent vibrational wavepackets of naphthacene dye with frequencies spanning 170−1600 cm −1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 84 publications
(162 reference statements)
3
23
0
Order By: Relevance
“…In other words, VC rapidly dephases since structures continuously evolve along the xOOP coordinate. This is a similar picture of the nested free energy crossing model in ultrafast electron transfer reaction, experimentally reported recently using ultrafast TA [54, 55] . After all structural changes are finished, the possible factors that can determine the dephasing time are vibrational relaxation and anharmonicity.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…In other words, VC rapidly dephases since structures continuously evolve along the xOOP coordinate. This is a similar picture of the nested free energy crossing model in ultrafast electron transfer reaction, experimentally reported recently using ultrafast TA [54, 55] . After all structural changes are finished, the possible factors that can determine the dephasing time are vibrational relaxation and anharmonicity.…”
Section: Resultssupporting
confidence: 70%
“…Furthermore, it provides deeper insights into the reaction mechanism of the excimer formation. Typically, vibrational dephasing in the excited state can be affected by several factors, such as 1) population decay of the state where VCs are generated, [53] 2) vibrational relaxation (vibrational cooling or intramolecular vibrational redistribution), [51] 3) (an)harmonicity of the potential [60] , 4) vibronic coupling of the reaction [55] . Here, the first factor can easily be ruled out, because excimer formation is not simple population kinetics between the two diabatic states and also not as an internal conversion (see below), for instance, from the S 2 to S 1 states.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, vibrational dephasing in the excited state can be affected by several factors, such as 1) population decay of the state where VCs are generated, [53] 2) vibrational relaxation (vibrational cooling or intramolecular vibrational redistribution), [51] 3) (an)harmonicity of the potential [60] , 4) vibronic coupling of the reaction. [55] Here, the first factor can easily be ruled out, because excimer formation is not simple population kinetics between the two diabatic states and also not as an internal conversion (see below), for instance, from the S 2 to S 1 states. We propose that vibronic coupling can play a primary role in the ultrafast excimer formation, which means that the xOOP mode acts as a promotor mode.…”
Section: Resultsmentioning
confidence: 99%
“…This is a similar picture of the nested free energy crossing model in ultrafast electron transfer reaction, experimentally reported recently using ultrafast TA. [54,55] After all structural changes are finished, the possible factors that can determine the dephasing time are vibrational relaxation and anharmonicity. Especially, in order to investigate the effect of anharmonicity, a two-dimensional Raman technique is required to get information about coupling between vibrations, [61,62] but this is not the main interest in this work and will be investigated in the future.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, it has been found that structural aspects such as the intramolecular vibration and solute–solvent interactions can play a governing role in ET reactions. 99,138 Therefore, ET reactions need to be investigated in terms of the structures of reactants and surrounding solvent cages as well as energetics. In this sense, an experiment in which fs-TRXL is combined with spectroscopic methods can be one of the powerful approaches used to accomplish the goal of controlling ET reactions.…”
Section: Charge Distribution and Electron Transfermentioning
confidence: 99%